Modification the Oxalic Co-precipitation Method on a Novel Catalyst Cu/Zn/Al2O3/Cr2O3 for Autothermal Reforming Reaction of Methanol - Cheng-Hsin Kuo; Ho-Shing Wu; Donny Lesmana (Bulletin of Chemical Reaction Engineering & Catalysis, 2013)
This study addresses the catalytic performance of Cu/ZnO/Al2O3/Cr2O3 in low-temperature of autothermal reforming (ATR) reaction. Various operating conditions were used to decide the optimum reaction conditions: type of promoter (ZrO2, CeO2, and Cr2O3), precipitation temperature, precipitation pH, operation temperature, molar ratio of O2/CH3OH (O/C), and weight hourly space velocity (WHSV). The catalysts were prepared using the oxalic coprecipitation method. Characterization of the catalyst was conducted using a porosity analyzer, XRD, and SEM. The methanol conversion and volumetric percentage of hydrogen using the best catalyst (Cu/ZnO/Al2O3/Cr2O3) exceeded 93% and 43%, respectively. A catalyst prepared by precipitation at -5 oC and at pH of 1 converted methanol to 40% H2 and less than 3000 ppm CO at reaction temperature of 200 oC. The size and dispersion of copper and the degradation rate and turnover frequency of the catalyst was also calculated. Deactivation of the Cu catalyst at a reaction temperature of 200 oC occurred after 30 h. © 2013 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)